Oriented Zinc Oxide Nanocrystalline Thin Films Grown from Sol-Gel Solution - Pokharel, Jyotshna; Shrestha, Maheshwar; Zhou, Li Qin; Neto, Victor; Fan, Qi Hua (Journal of Coating Science and Technology, 2015)
Zinc oxide (ZnO) is a wide band gap (~3.37 eV) semiconductor. Thin film ZnO has many attractive applications in optoelectronics and sensors. Recently, nanostructured ZnO (e.g. ZnO quantum dot) has been demonstrated as a hyperbolic material; its dielectric function has opposite signs along different crystal axes within the mid-infrared, making it an interesting material for metamaterials and nanophotonics. Conventional sputtering deposition usually leads to the formation of polycrystalline ZnO films with randomly oriented grains and rough surface. This work demonstrated a solution-based process to grow ZnO thin films with highly oriented nanocrystals. Low-temperature plasmas were employed to modulate the microstructure and optical properties of the films. Such highly anisotropic nanostructured transparent semiconductor films may lead to interesting material properties in developing new optoelectronic devices.